QLTI-04. USING VARIANT ALLELIC FRACTION OF DRIVER MUTATIONS IN ADULT-TYPE DIFFUSE GLIOMA TO IMPROVE MGMT PROMOTER METHYLATION TESTING. (14th November 2022) - McCord, Matthew; Galbraith, Kristyn; Jamshidi, Pouya; Lukas, Rimas; Zhang, Hui; Jennings, Lawrence; Snuderl, Matija; Horbinski, Craig
Abstract: Methylation of the O 6 -methylguanine-DNA methyltransferase ( MGMT ) promoter predicts favorable response to temozolomide in adult-type diffuse gliomas. Accurate MGMT results require adequate tumor cellularity. Too many admixed non-neoplastic cells (which are always MGMT unmethylated) may cause false-negative results. Currently, 70% tumor cellularity, based on estimation by microscopy, is recommended for reliable testing. However, this is subjective, and few cases are actually excluded from testing, so there is a risk of false-negative MGMT results. Since adult-type diffuse gliomas usually have heterozygous driver mutations in nearly all tumor cells, including IDH1, IDH2, and/or TERT, we determined whether the variant allelic fraction (VAF) of these mutations could serve as a better quality control metric in MGMT assays. A discovery cohort consisted of 175 gliomas (112 IDH -wildtype, TERT -mutant GBMs, 34 IDH -mutant astrocytomas, and 29 oligodendrogliomas). A validation cohort consisted of 50 gliomas (32 GBMs, 11 IDH -mutant astrocytomas, 7 oligodendrogliomas); all cases had MGMT pyrosequencing and NGS data. Gliomas with average ≥ 10% methylation of 4 measured CpG sites on the MGMT promoter were considered positive, as per standard cutoffs. The discovery cohort showed positive correlation between VAF and MGMT methylation among all gliomas (slope=0.26, R 2 =0.034, P=0.014). The largest drop-off in MGMT methylation occurred with VAF < 13% (average MGMT of 4.77% versus 18.65% for VAF ≥ 13%, P=0.037). Among GBMs, only 1/7 (14.0%) with TERT VAF < 13% met the cutoff for MGMT promoter methylation, versus 39/105 (37.0%) with VAF ≥ 13%. Based on our previous study (PMID 33830235), approximately 36.5% of GBMs should be positive. The validation cohort showed a similar pattern, wherein gliomas with driver mutation VAF < 13% had average MGMT of 5.75% versus 14.94% for VAF ≥ 13%. In summary, our results suggest that glioma samples with driver mutation VAF below 13% are at higher risk of false-negative MGMT promoter methylation.